Efficacy of PARP Inhibitors in the Treatment of Ovarian Cancer: A Literature-Based Review - Vikas Goswami; Venkata Pradeep Babu Koyyala; Sumit Goyal; Manish Sharma; Varun Goel; Nilesh Dhamne; Udip Maheshwari; Atul Sharma (Asian Journal of Oncology, 2019)
Poly (ADP-ribose) polymerase (PARP) inhibitors are a unique class of therapeutic agents that focus on tumors with deficiencies in the homologous recombination DNA repair mechanism. Genomic instability outlines high-grade serous ovarian cancer, with 50% of all tumors displaying defects in the important DNA repair mechanism of homologous recombination. Earlier research studies have demonstrated considerable efficiency for PARP inhibitors in patients with germ line breast-related cancer antigens 1 and 2 (BRCA-1/BRCA-2) mutations. It has also been observed that BRCA wild-type patients with other defects in the homologous recombination repair mechanism get benefited from this therapy. Companion homologous recombination deficiency (HRD) scores are being developed to guide the selection of patients that are most likely to benefit from PARP inhibition. The selection of PARP inhibitor is mainly dependent upon the number of prior therapies and the presence of a BRCA mutation or HRD. The identification of cases which are most likely to get benefited from PARP inhibitor therapy in view of HRD and other biomarker assessments is still challenging. The purpose of this review is to focus and describe the current evidences for PARP inhibitors in ovarian malignancy, their mechanism of action, and the outstanding issues, including the rate of long-term toxicities and the evolving resistance.